Analisis Variabel yang Memengaruhi Kemiskinan Rumah Tangga Provinsi Kepulauan Riau 2023 - Naufal, Anis; Suwandana, Endan (Publikasi Penelitian Terapan dan Kebijakan, 2024)
Poverty alleviation is the main goal in the SDGs, RPJPN 2005 - 2025 and RPJMN 2020-2024. Poverty research has been carried out before, but very rarely has it discussed household poverty in the Riau Islands Province. This research aims to identify variables that significantly influence household poverty status in the Riau Islands in 2023. The data used in this research is Susenas data for March 2023 with binary logistic regression analysis method. The research results show that the age of the head of the household (KRT), number of household members, marital status of the KRT, education of the KRT, employment of the KRT, internet access of the KRT, and residence ownership status significantly influence household poverty status. In overcoming poverty, the government can implement family planning programs, socialize the prevention of early marriage, educational programs such as educational assistance, provide business opportunities, programs to improve farmers' welfare, and expand the internet network.